2018
DOI: 10.1186/s12883-018-1022-7
|View full text |Cite
|
Sign up to set email alerts
|

Right-to-left shunt and subclinical ischemic brain lesions in Chinese migraineurs: a multicentre MRI study

Abstract: BackgroundMigraine is considered as a risk factor for subclinical brain ischemic lesions, and right-to-left shunt (RLS) is more common among migraineurs. This cross-sectional study assessed the association of RLS with the increased prevalence of subclinical ischemic brain lesions in migraineurs.MethodsWe enrolled 334 migraineurs from a multicentre study from June 2015 to August 2016. Participants were all evaluated using contrast-enhanced transcranial Doppler, magnetic resonance imaging (MRI), and completed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…The prevalence rate of DWMHs in our study was 58.2%, which is slightly higher than that reported in previous studies (7), despite the younger age (39.3 ± 11.7 years) of our participants. The overall prevalence of RLS in our study (48.5%) was similar to that of our previous work (46.1%) ( 10), but lower compared to other studies (9,18). Also, a higher prevalence rate of RLS in patients diagnosed with MwA, as reported in the literature (10,19), was not found in our study.…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence rate of DWMHs in our study was 58.2%, which is slightly higher than that reported in previous studies (7), despite the younger age (39.3 ± 11.7 years) of our participants. The overall prevalence of RLS in our study (48.5%) was similar to that of our previous work (46.1%) ( 10), but lower compared to other studies (9,18). Also, a higher prevalence rate of RLS in patients diagnosed with MwA, as reported in the literature (10,19), was not found in our study.…”
Section: Discussionsupporting
confidence: 85%
“…[1012] Consistently, migraine patients may display an increased subclinical vascular burden at magnetic resonance imaging mainly in the posterior territory. [13] Nevertheless, recent reports refuted this finding, also in patients with right-to-left shunts (RLS)[14] or with migraine with aura [15]. Right-to-left shunts.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have had the opposite results. In 2018, a multicentre study involving 334 migraine patients in China found that right-to-left shunts were not associated with WMLs in migraine patients 17 . Another study conducted in 139 children and adolescents with migraine in the United States in 2013 showed that WMLs in migraine patients did not correlate to the existence of right-to-left shunts, the degree of rightto-left shunts, or the subtype of migraine 18 .…”
Section: Discussionmentioning
confidence: 99%